IMPLIKATUR PERCAKAPAN DALAM KOMIK WEBTOON 304th STUDY ROOM KARYA FELICIA HUANG SEBUAH TINJAUAN PRAGMATIK - Robiatun Adawiyah Siregar; Mangatur Sinaga; Charlina Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is entitled the conversational implicature in the comic webtoon 304th study room by Felicia Huang, a pragmatic review. The purpose of this research is to describe and analyze the types and functions of conversational implicature contained in the comic webtoon 304th study room by Felicia Huang. The method used is descriptive qualitative. Data collection techniques using reading techniques, and note taking techniques. Data analysis technique is in the form of data transcription. The results of the study are firstly there are three types of conversational implicature, namely a) special conversation implicator which consists of 21 data b) general conversation implicator, totaling 14 data c) conversation scale with 3 data scale; secondly, the implicature function in the webtoon comic 304th study room by Felicia Huang, namely a) the implicature function approves 1 data, b) the implicature function commands 5 data, c) the implicature function requests 6 data, d) the implicature function confirms 8 data, e) functions the implicature complains 7 data, f) the implicature function insinuates 6 data and g) the implicature function states 5 data.Key Words: Implications, Types of Conversation Implications, Implications Function, Webtoon 304th Study Room by Felicia Huang